Design of E-Form API Development Using PHP Framework CodeIgniter 3 for the Nusantara Online NAS Certification Application - Nasution, Bagas; Suryadi, Suryadi (Universitas Teuku Umar, 2024)
This article explains the design of backend API development using the PHP Framework CodeIgniter 3 in an online certification application developed by PT Nusatek. The application aims to facilitate the online certification process by collaborating with various Professional Certification Bodies (LSP) in accordance with BNSP standards. CodeIgniter 3 was chosen as the main development framework due to its execution speed and comprehensive support for API development. The article highlights CodeIgniter as an efficient solution to meet backend development needs, combined with the use of Composer. The main focus of this article is on seamless integration with various LSPs, with an emphasis on secure data exchange between the application and its partners. The data retrieval process, such as obtaining the applicant's full name, gender, contact information, etc., is also discussed. This article aims to provide an in-depth insight into the development steps adopted by me as the developer. It is expected that this article can offer valuable contributions to individuals involved in developing similar applications.